Seismic response and shear mechanism of engineered cementitious composite (ECC) short columns. (1st August 2019) - Zhang, Yangxi; Deng, Mingke; Dong, Zhifang
Highlights: The seismic response of RECC and SRECC short columns is investigated. Improvement in failure modes, shear strength and plastic deformation capacity of the ECC columns were observed. Fiber bridging effect of ECC effectively contributed to the shear strength. Prediction modes for the shear strength of ECC short columns were proposed. Abstract: The seismic behavior of reinforced engineered cementitious composite (RECC) short columns and H-steel reinforced engineered cementitious composite (SRECC) short columns has been investigated by the combined constant axial compression and lateral cyclic load. Two RECC short columns, two SRECC short columns and a reinforced concrete (RC) short column were examined in this study. The test results indicate that the crack control capacity, shear strength, plastic deformation capacity and the energy dissipation capacity of the RECC short columns were much higher than those of the RC short column with identical axial loads. The behavior of the RECC columns and SRECC columns was dominated by shear, and bond failure was observed in the SRECC columns. However, the plastic deformability of the SRECC columns remained much higher than that of the RECC columns. In comparison to the RECC columns, the lateral displacement and cumulative energy dissipation of the SRECC columns were improved by 41 ∼ 72% and 134 ∼ 241%, respectively, at the ultimate state. Based on the test results, the shear mechanism of the ECC short columns was analysed by the truss-arch model. Furthermore, applicative design methods based on the current codes are proposed to calculate the shear strength of ECC short columns.